Climate Adaptation Interventions in Coastal Areas: A Rapid Review of Social and Gender Dimensions - Prakash, Anjal; McGlade, Katriona; Roxy, Mathew Koll; Roy, Joyashree; Some, Shreya; Rao, Nitya (Frontiers in Climate, 2022)
In this paper, we present the results of a rapid review of the literature on gender and coastal climate adaptation. The IPCC’s 2019 Special Report on Oceans and Cryosphere (SROCC) highlighted some of the major ways in which gender inequality interacts with coastal climate change. However, the report does not consider how gender interacts with adaptation interventions. This review was driven by the need to understand these dynamics in more detail as well as deepen the understanding of how coastal climate adaptation affects the attainment of Sustainable Development Goal (SDG) 5, for gender equality and the empowerment of women and girls. Our analysis is based on a screening of over 1000 peer-reviewed articles published between 2014-2020. The results were strongly populated by natural science publications leading to very low coverage of gender as a social dimension of adaptation. Of the papers reviewed, a mere 2.6% discussed gender and often only in a cursory way. While the literature surveyed does not allow us to close the gap present in the SROCC in any meaningful way, the results do provide important new insights from the literature that does exist. Of particular note is the fact that adaptation measures may have positive and negative gender outcomes currently invisible under the SDG5 framework. We conclude that there is a need to collect gender-disaggregated data on coastal adaptation efforts and to review SDG5 targets and indicators to ensure that the gender dimensions of climate adaptation are fully captured and accounted for.